Catalytic Precision Polymerization: Rare Earth Metal‐Mediated Synthesis of Homopolymers, Block Copolymers, and Polymer Brushes. Issue 20 (22nd August 2014) - Soller, Benedikt S.; Zhang, Ning; Rieger, Bernhard; Buchmeiser, Michael R.
<x xml:space="preserve">Abstract</x> Recent studies have shown that rare earth metal‐mediated group transfer polymerization (REM‐GTP) can be applied to a variety of polar monomers, besides the classic (meth)acrylates or (meth)acrylamides, giving access to new polymeric materials. This article highlights progress in this new field and gives a current overview of the initiation and propagation of vinylphosphonates, the extension to Michael‐type nitrogen‐coordinating monomers, and application to block copolymers, statistical copolymers, and 2D and 3D structures. Based on molecular understanding and high‐precision synthesis, REM‐GTP represents a versatile method for the preparation of new materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>